Synthesis and Anticancer Activity of 3-[5-Amino-6-(2,3-dichlorophenyl)-[1,2,4]triazin-3-yl]-6,8-dibromo-2-substituted-3H-quinazolin-4-one - Girija, K.; Selvam, P.; Nagarjan; Chandramohan, M. (Asian Journal of Chemistry, 2016)
A series of novel 6,8-dibromo-2,3-disubstituted quinazolin-4(3H)-ones have been synthesized by condensing the primary amino group of lamotrigine with benzoxazin-4-one. The structure of the synthesized compounds was elucidated by spectral analysis (IR, NMR and mass). Investigation of anticancer activity was done against nine types of human cancer in 60 different strains of tumour cell line.